(untitled) (Studia Prawnicze / The Legal Studies, 2009)
Współczesne ustawodawstwa karnoprocesowe przewidują tryby postępowania, które różnią się w swym przebiegu od postępowania uznanego za zwyczajne w danym systemie procesowym. Są to postępowania szczególne. Do nich należy tryb nakazowy. Stanowi on postępowanie szczególne drugiego stopnia o „zredukowanym” charakterze i najbardziej posuniętym odformalizowaniu wśród powyższych trybów. In many countries the modern criminal law proceedings provide a main procedure and a number of special procedures. Those special types of procedure differ in their course from the main procedure in the particular criminal proceeding. One of them is the procedure for penal order verdicts. The article discusses the workings of the procedure for penal order verdicts from practical side. But first the author presents the regulations in the “Code of Penal Procedure” from 1997 referring to this procedure. Thelegislator assumed the possibility of the participation of the defendant and his attorney-at-law in the court session, although the public prosecutor was obliged to take part in the session. The decision given by the court at first instance was a penal order, i.e. not a verdict. A penal order might impose punishment in the form of limited imprisonment or fine, according to Article 502 of the “Code of Penal Procedure” from 1997, and only the following subset of legal consequences of the offense, either on their own or in a combination: compensation and forfeiture of goods. The pronouncement of the penal order was made in public to both parties and the audience. The author brings the attention to the fact that, the penal order must have contained the reason for the decision in writing. The article presents proposals de lege lata and the need for changes de lege ferenda in the procedure. After the major, fundamental amendment of the “Code of Penal Procedure” from 1997, which took place on 1 of July 2003, the parties and the audience may not participate in the procedurefor penal order verdicts court session. Thesession is “closed” for any entitled persons. The decision given by the court at first instance is not a penal order but a penal order verdict, which shall be communicated to the public prosecutor, defendant and his representative by the way of delivering its certified copy. The content of a penal order verdict issued during a court session is made available to the public by the way of depositing a certified copy of such order for seven days in the court’s secretariat, an action to be mentioned in the minutes of the court session. This institution gives rise to the controversy because the promulgation is not really public. A judge may impose punishment in the form of fine or limited imprisonment and any legal consequences of the offense, which the “Code of Penal Procedure” from 1997 assumes, either on their own or in combination. The verdict may not contain the reason for the decision. The author suggests that these changes were intended by legislator to accelerate the procedure for penal order verdicts. In the second part the article presents the results of author’s researches connected with using this procedure in practice. Information gathered in the Ministry of Justice from year 2000 to 2007 connected with penal orders or penal order verdicts has been analyzed. Special attention was paid to the amount of penal orders and penal order verdicts issued before and after the major, fundamental amendment of the “Code of Penal Procedure" from 1997, which took place on 1st of July 2003. The analysis of results of researches permits to conclude that the courts of first instance use this procedure more often after the amendment. It is a significant conclusion because cases in this procedure can be finished faster, therefore courts using this procedure can sentence in more cases than earlier.